2017
DOI: 10.1002/ajim.22761
|View full text |Cite
|
Sign up to set email alerts
|

Work‐related mortality in the US fishing industry during 2000‐2014: New findings based on improved workforce exposure estimates

Abstract: Background Commercial fishing is a global industry that has been frequently classified as high-risk. The use of detailed surveillance data is critical in identifying hazards. Methods The purpose of this study was to provide updated statistics for the entire US fishing industry during 2010–2014, generate fleet-specific fatality rates using a revised calculation of full-time equivalent estimates, and examine changes in the patterns of fatalities and in risk over a 15-year period (2000-2014). Results During 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Fishing workers were also found to have high rates of OROD. Commercial fishing is one of the most hazardous occupations in the United States with a work‐related injury fatality rate 25 times higher than the national average . Nonfatal injuries and musculoskeletal disorders among fishermen are common.…”
Section: Discussionmentioning
confidence: 99%
“…Fishing workers were also found to have high rates of OROD. Commercial fishing is one of the most hazardous occupations in the United States with a work‐related injury fatality rate 25 times higher than the national average . Nonfatal injuries and musculoskeletal disorders among fishermen are common.…”
Section: Discussionmentioning
confidence: 99%
“…Sinking vessels cause the most fatalities in the industry; however, falling from a fishing vessel is a serious hazard responsible for the second highest number of commercial fishing–associated fatalities ( 2 , 3 ). CDC’s National Institute for Occupational Safety and Health (NIOSH) analyzed data on unintentional fatal falls overboard in the U.S. commercial fishing industry to identify gaps in the use of primary, secondary, and tertiary prevention strategies.…”
mentioning
confidence: 99%
“…Krenz et al [22] also found the "Jensen" System useful for activity classification for claims. lucas et al [23] applied a framework based on our system to code processes specifically related to long-liners and trawlers.…”
Section: How Did Other Researchers Use the Studies For Comparisons?mentioning
confidence: 99%
“…Based on the trend's analyses of fatalities in fishing in Study 2, the preventive programs seem to have good effects. Still, the authors call for continued effort to improve safety in fishing in all the studies [23,30,36].…”
Section: How Did Other Researchers Use the Studies For Comparisons?mentioning
confidence: 99%